Biodecoloration of Reactive Black 5 by the methylotrophic yeast Candida boidinii MM 4035 - Martorell, María Martha; Pajot, Hipolito Fernando; Ahmed, Pablo Miguel; Castellanos, Lucia Ines (Journal of Environmental Sciences)
Azo dyes are extensively used in textile dyeing and other industries. Effluents of dying industries are specially colored and could cause severe damage to the environment. The anaerobic treatment of textile dying effluents is nowadays the preferred option, but it could generate carcinogenic aromatic amines. Recently, yeasts have become a promising alternative, combining unicellular growth with oxidative mechanisms. This work reports the characterization of the first methylotrophic yeast with dye decolorizing ability, Candida boidinii MM 4035 and some insights into its decoloration mechanism. The analysis of two selected media revealed a possible two stages mechanism of Reactive Black 5 decoloration. In glucose poor media, decoloration is incomplete and only the first stage proceeds, leading to the accumulation of a purple compound. In media with higher glucose concentrations, the yeast is able to decolorize totally an initial concentration of 200 mg/L. The entire process is co-metabolic, being largely dependent on glucose concentration but being able to proceed with several nitrogen sources. Manganese dependent peroxidase but not laccase activity could be detected during decoloration. Aromatic amines do not accumulate in culture media, supporting an oxidative decoloration mechanism of unknown ecophysiological relevance. Fil: Martorell, María Martha. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Pajot, Hipolito Fernando. Universidad San Pablo Tucumán; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Ahmed, Pablo Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Gobierno de Tucumán. Ministerio de Desarrollo Productivo. Estación Experimental Agroindustrial Obispo Colombres; ...